Membentuk Karakter Anak Usia Dini Melalui Permainan Tradisional - Ilmi Sabrina Khoirunnisa (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2021)
This article aims to determine the benefits of traditional children's games in the formation of early childhood character. This is motivated by the phenomenon of changes in children's playing activities today, which more often play modern games that are synonymous with the use of technology such as video games and online games. As a result, traditional children's games began to be forgotten and became foreign to children. In addition, the level of addiction to modern games in children is also high so that it has a bad effect on children's habits and behavior. This paper describes the impact that occurs in children when addicted to playing games which results in the character that will be awakened in early childhood. In addition, it also compares the influence of modern games with traditional games on the formation of early childhood character. Restoring traditional children's games as children's games today can be an alternative to create a generation of superior characters.